2004
DOI: 10.1093/humrep/deh079
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of menstrual cycle pattern, body mass index, hormone levels and polycystic ovaries at age 15 years for oligo-amenorrhoea at age 18 years

Abstract: Oligomenorrhoea at age 18 years is better predicted by menstrual cycle pattern at age 15 years than by LH or androgen concentrations or PCO at this age. Not only obese, but also normal weight oligomenorrhoeic, adolescents have a high risk of remaining oligomenorrhoeic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(70 citation statements)
references
References 41 publications
4
61
1
4
Order By: Relevance
“…Delayed puberty was considered to have occurred by the absence of breast development by the time the girl was 13 years old. Menstrual disorders were assessed only in girls whose gynaecological age was at least 2 years (24,25,26). Data on each girl's pubertal development and menstrual history were obtained retrospectively by interviewing each girl and her mother and by reviewing each girl's medical record.…”
Section: Methodsmentioning
confidence: 99%
“…Delayed puberty was considered to have occurred by the absence of breast development by the time the girl was 13 years old. Menstrual disorders were assessed only in girls whose gynaecological age was at least 2 years (24,25,26). Data on each girl's pubertal development and menstrual history were obtained retrospectively by interviewing each girl and her mother and by reviewing each girl's medical record.…”
Section: Methodsmentioning
confidence: 99%
“…7 Precocious puberty, early adrenarche presenting with early pubic hair development or oligomenorrhoea may also be presenting symptoms. [8][9][10][11][12] With regard to the potential etiology of PCOS, it is thought that exposure to excess androgens in early fetal life may increase the likelihood of developing PCOS in later years. 13 Various clinical and phenotypic presentations may precede the diagnosis of PCOS and include, but are not limited to, hyperandrogenism, menstrual irregularity, olio/anovulation and infertility.…”
Section: Reproductive Features In Women With Pcosmentioning
confidence: 99%
“…In these girls, body mass index (BMI) may represent the best predictor of unbound testosterone levels, much more than luteinizing hormone (LH) and insulin levels, and the Tanner stage (27). Large population-based studies have also shown that half of oligomenorrheic girls may have significantly increased LH and androgen levels (28), although this finding still remains controversial, since other studies performed in healthy normal-weight girls with anovulatory regular menses showed that they were characterized by a significantly higher androgen levels in comparison with those with ovulatory menses (29). Intriguingly, longitudinal studies have shown that adolescent serum androgen levels may be preserved into adulthood and are associated with menstrual dysfunction, which suggests a potential risk to develop PCOS (30).…”
Section: Arguments In Favor Of the Definition Of Secondary Pcosmentioning
confidence: 99%